2022
DOI: 10.3390/jtaer17040067
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Driven Optimal Strategies for Supply Chain Finance Based on a Tripartite Game Model

Abstract: Applying blockchain to supply chain financing is an effective way to solve the problems of financing difficulties, high financing costs, and slow financing for small and medium-sized enterprises (SMZEs). Using evolutionary game theory, this study constructs a tripartite game model and analyzes the influence of blockchain technology on the evolutionary stability strategies for financial institutions (FIs), core enterprises (CEs), and SMZEs, in which the default losses of CEs and SMZEs are assumed to be dynamic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Some scholars have also studied a system that includes a secondary supply chain and financial institutions. Luo, Y. et al [29] compared the game behavior of traditional supply chain finance and supply chain finance participants in the blockchain and the difference between the mixed decision Nash equilibrium with regard to increasing the blockchain incentives and penalties. It was found that financiers and providers were more likely to cooperate when the blockchain rewards and penalties were increased.…”
Section: Supply Chain Finance Based On Blockchain Technologymentioning
confidence: 99%
“…Some scholars have also studied a system that includes a secondary supply chain and financial institutions. Luo, Y. et al [29] compared the game behavior of traditional supply chain finance and supply chain finance participants in the blockchain and the difference between the mixed decision Nash equilibrium with regard to increasing the blockchain incentives and penalties. It was found that financiers and providers were more likely to cooperate when the blockchain rewards and penalties were increased.…”
Section: Supply Chain Finance Based On Blockchain Technologymentioning
confidence: 99%
“…Sun et al (2021) constructed a two‐party accounts receivable evolutionary game model of the SME and the financial institution, and calculated the change scenarios of evolutionary stabilization strategies before and after applying blockchain technology, which is found to effectively mitigate the operational risk of financial institutions by maintaining credit defaults in a high‐risk state. Su et al (2022) analyzed the impact of blockchain technology on the stability strategies of a tripartite evolutionary game with financial institutions, core firms, and SMEs, and found that increases in the amount of default losses and receivables can reduce the default probability.…”
Section: Introductionmentioning
confidence: 99%
“…Although Wang et al (2019) and Lin and Peng (2021) examined this issue and emphasized on the illegal financing access of SMEs, the notion that a majority of supply chain finance risk exposure arises from the embezzlement of loans by financing firms and the operational risks of unauthorized discharge of pledge by supporting enterprises has been ignored. Sun et al (2021) and Su et al (2022) analyzed the role of blockchain on accounts receivable financing, but the features of the role of blockchain technology in inventory pledge financing require separate research since great differences exist in involved subjects and financing approaches. Considering that the inactivity of financial institutions may induce violations of logistics enterprises and SMEs, their excessive control will incur a reduction in profits.…”
mentioning
confidence: 99%
“…As trust in these technologies is established [3], BC enhanced with SC has the potential to impact various fields such as finance, e-commerce, supply chain management, education, voting, or healthcare [4,5]. Such systems can contribute to improving security [6], transparency, and efficiency in the decentralized context of smart applications (dApps).…”
Section: Introductionmentioning
confidence: 99%